The Composition of Growth Matters for Poverty Alleviation - Loayza, Norman V.; Raddatz, Claudio (2012)
This paper contributes to explain the cross-country heterogeneity of the poverty response to changes in economic growth. It does so by focusing on the structure of output growth itself. The paper presents a two-sector theoretical model that clarifies the mechanism through which the sectoral composition of growth and associated labor intensity can affect workers' wages and, thus, poverty alleviation. Then, it presents cross-country empirical evidence that analyzes, first, the differential poverty-reducing impact of sectoral growth at various levels of disaggregation, and, second, the role of unskilled labor intensity in such differential impact. The paper finds evidence that not only the size of economic growth but also its composition matters for poverty alleviation, with the largest contributions from unskilled labor-intensive sectors (agriculture, construction, and manufacturing). The results are robust to the influence of outliers, endogeneity concerns, alternative explanations, and various poverty measures.